The Future of lndustrial Relations : Proceedings of the Second Bargaining Group Conference - Morin, Denis (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "The Future of lndustrial Relations : Proceedings of the Second Bargaining Group Conference," edited by Harry C. Katz.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z